2006
DOI: 10.1111/j.1464-410x.2006.06514.x
|View full text |Cite
|
Sign up to set email alerts
|

The contemporary management of renal and ureteric calculi

Abstract: I have put a mini‐review into this section this month; this is from one of the leading experts in this field, and gives an up‐to‐date overview of the contemporary management of renal and ureteric calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 59 publications
0
88
0
1
Order By: Relevance
“…While staghorn is the extreme of large stone size, any stone over 2 cm is associated with an inferior outcome when treated with SWL [8][9][10][11] . Larger stones usually require more procedures and have increased complications such as obstruction from steinstrasse or larger fragment passage.…”
Section: Patient Selectionmentioning
confidence: 99%
“…While staghorn is the extreme of large stone size, any stone over 2 cm is associated with an inferior outcome when treated with SWL [8][9][10][11] . Larger stones usually require more procedures and have increased complications such as obstruction from steinstrasse or larger fragment passage.…”
Section: Patient Selectionmentioning
confidence: 99%
“…On the other hand, Singh et al (22) found that the rate of complete stone-free status was 85.7% for RIRS treatment and 54.3% for ESWL treatment in lower pole stones with sizes between 10 mm and 20 mm and they observed that RIRS was markedly superior. There are other studies that report the superiority of RIRS over ESWL in lower pole stones (23)(24)(25). In an examination of these studies, it was concluded that RIRS is superior to ESWL with respect to providing complete stonefree status as the size of the stone increases; it gives rise to less need for additional intervention; and morbidity rates are higher than in ESWL, but this is not statistically significant.…”
Section: Discussionmentioning
confidence: 92%
“…In Australia, the annual incidence of stone disease is estimated to affect 131 per 100,000 population [1]. Furthermore, in those with a history of upper urinary tract stones, studies have shown a recurrence rate of 50% within the subsequent 5-10 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…The gender difference has always been at least partly attributed to differences in excretory function, with men excreting more oxalate in the urine, and women more citrate, which is protective against stone formation [2]. In addition, increased animal protein intake has been associated with higher rates of calcium oxalate stone formation, with a 5-year randomised trial revealing a protective effect of reduced animal protein and salt intake when compared with a low-calcium diet in recurrent stone formers [4].…”
Section: Introductionmentioning
confidence: 99%